2013
DOI: 10.1055/s-0033-1345177
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Serum Markers of Erythropoiesis during 6 Days of Racing in Highly Trained Cyclists

Abstract: The athlete biological passport for the fight against doping is currently based on longitudinal monitoring for abnormal changes in cellular blood parameters. Serum parameters related to altered erythropoiesis could be considered for inclusion in the passport. The aim of this study was to quantify the changes in such parameters in athletes during a period of intense exercise. 12 highly trained cyclists tapered for 3 days before 6 days of simulated intense stage racing. Morning and afternoon blood samples were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 33 publications
6
39
1
Order By: Relevance
“…After the initial resting phase (days 1–3), the race period starts (days 4–12). Days 6–8 of this period show the lowest GH‐scores, which correlates to the observed plasma volumes which showed the highest values on these days …”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…After the initial resting phase (days 1–3), the race period starts (days 4–12). Days 6–8 of this period show the lowest GH‐scores, which correlates to the observed plasma volumes which showed the highest values on these days …”
Section: Resultssupporting
confidence: 71%
“…Haemoglobin mass was measured in each subject in duplicate at the beginning of the study. The true haemoglobin mass for each time point was calculated taking into account the exact loss of haemoglobin due to blood sampling …”
Section: Methodsmentioning
confidence: 99%
“…Similar to our findings, in a crossover design Keiser et al also implemented variable training loads set to elicit the same relative cardiac strain in both their hot and cool training conditions and also found that none of the heat adaptations (eg, increased PV) correlated to changes in exercise performance. Indeed, although not always shown, increased training load or multi‐day competition in already hypervolemic elite endurance athletes (international level cyclists) has been shown to augment PV by 5%‐20% in as little as 6‐7 days regardless of the heat load . Importantly, the current study's outcomes, in combination with training effects on PV, suggest that many of the previously published HA studies without an exercise control group in mild/cool conditions matched for relative cardiac work stress, may be showing outcomes that are due to both exercise stress, and metabolic heat.…”
Section: Discussionmentioning
confidence: 50%
“…Biomarkers to adjust for vascular shifts present an alternative approach. Previously, ALB was identified as a candidate PV marker ; however, ALB is influenced by altitude, exercise and nutritional status . As such, it is unlikely that an individual marker will present with sufficient stability and low variability, which would be required to accurately and reliably identify PV shifts in an anti‐doping context.…”
Section: Discussionmentioning
confidence: 99%